Refocusing IBD Patient Management: Personalized, Proactive, and Patient-Centered Care. (October 2018) - Siegel, Corey
Abstract Medications are available that can be highly effective for the treatment of inflammatory bowel disease (IBD). However, there are multiple barriers in place to offer these treatments to the right patients at the right time. In addition to obstacles created by payers, there are concerns over medication side effects by patients and providers, and the logistic challenges of navigating the maze of initiating someone on biological therapy. As a gastroenterology community, we need to push the field forward for the sake of our patients. Current and future drug development for IBD is exciting, but we need to optimize what we have now to the best of our ability. When used appropriately and early enough in the disease course, our current medications can heal the bowel and prevent complications from developing. While recognizing that all patients do not need early intensive therapy, we need to identify the appropriate patients for more aggressive treatments. This article will describe how we can improve patient management now by shifting our focus to using a personalized, proactive, and patient-centered approach in our delivery of IBD care.